Analysis of diagnostic laparoscopy in chronic right iliac fossa pain - Vaishnav, Umesh; Patel, Harshad S. (International Surgery Journal, 2017)
Background: Chronic right iliac fossa pain with normal radiological and laboratory finding is common indication for diagnostic laparoscopy by general surgeon. Most common cause of chronic right iliac fossa pain is appendicitis. Laparoscopic appendectomy is commonly done in diagnostic laparoscopy if other cause is not found. Methods: Patients of all the age group and either gender, undergone diagnostic laparoscopy for chronic right iliac fossa pain longer than 3 months with normal radiological finding in the surgical department. Diagnostic and therapeutic role of laparoscope was assessed. Results: 83% patients were showing visible positive finding on diagnostic laparoscopy. On follow up after 1 month, 90% patients show reliving of pain. Conclusions: Diagnostic laparoscopy is minimal invasive surgical procedure. It is useful when other pathological and radiological investigations are inclusive.